Alopecia areata: Dermatoscopic differences between pediatric and adult patients - Al Chalabi, Qasim; Fathi, Haitham; Al Mallah, Mohammed (Journal of Pakistan Association of Dermatologists, 2023)
Objectives: To compare and analyze the dermatoscopic features of alopecia areata and its association with the severity of the disease, clinical patterns, and nail involvement between children and adults. Patients and methods: A multi-center cross-sectional study was conducted in the Departments of Dermatology at Al-Salam and Ibn Sena Teaching Hospitals, Mosul, Iraq. During the period from Oct. 2021 to Oct. 2022. Ninty-sex children and 171 adult patients with alopecia areata were examined and assessed by dermatoscope, and the findings were recorded, evaluated, and tabulated‎. Results: Pediatric alopecia areata was more common in females (M: F 1:1.6) while adult males were more likely to have the disease (M: F 1.7:1). The mean age (± SD) of the presentation was of 9.7 ± 3.3 years for children and 29.9 ± 9.8 years for adults. Multiple patches of alopecia areata were found in 59.3% of pediatric patients and 68.4% of adult patients, while the reticular type was the least common variant among children and adults. Yellow dots (81.2%) were the most frequent trichoscopic sign in children followed by short vellus hairs (71.8%), compared with adults who showed short vellus hairs (68.4%) followed by yellow dots (66.6%). Upright hairs in the S1 grade were more found in adults than in children, while yellow dots were seen in children more than adults in the S2 grade. However, short vellus hairs and exclamation mark hairs showed significant changes among adult patients in the S3 group. Broken hairs were more common among children cases in the S4 group. Yellow dots, exclamation mark hairs, and triangular hairs were correlated with severe clinical variants in adults. While in children only broken hairs were correlated with severe clinical patterns of alopecia areata. Nail involvement was associated with severe forms of the disease (p-value <0.05) in children and adult patients. Conclusion: Yellow dots and broken hairs were the most common dermatoscopic finding in children. In adult patients, short vellus hairs were the most frequent sign followed by yellow dots. Nail changes were correlated with disease severity in both adults and children.